49.4.9 problem 2(b)

Internal problem ID [7620]
Book : An introduction to Ordinary Differential Equations. Earl A. Coddington. Dover. NY 1961
Section : Chapter 2. Linear equations with constant coefficients. Page 52
Problem number : 2(b)
Date solved : Monday, January 27, 2025 at 03:07:47 PM
CAS classification : [[_2nd_order, _missing_x]]

\begin{align*} y^{\prime \prime }+y^{\prime }-6 y&=0 \end{align*}

With initial conditions

\begin{align*} y \left (0\right )&=0\\ y^{\prime }\left (0\right )&=1 \end{align*}

Solution by Maple

Time used: 0.010 (sec). Leaf size: 16

dsolve([diff(y(x),x$2)+diff(y(x),x)-6*y(x)=0,y(0) = 0, D(y)(0) = 1],y(x), singsol=all)
 
\[ y = \frac {\left ({\mathrm e}^{5 x}-1\right ) {\mathrm e}^{-3 x}}{5} \]

Solution by Mathematica

Time used: 0.014 (sec). Leaf size: 21

DSolve[{D[y[x],{x,2}]+D[y[x],x]-6*y[x]==0,{y[0]==0,Derivative[1][y][0] ==1}},y[x],x,IncludeSingularSolutions -> True]
 
\[ y(x)\to \frac {1}{5} e^{-3 x} \left (e^{5 x}-1\right ) \]